Out of Silence: A Pianist's Yearbook - Tomes, Susan (Rochester Boydell & Brewer, 2010)
Out of Silence is a diary of a year in Susan Tomes's life as a performer. Taking as its inspiration Schumann's remark that 'I am affected by everything that goes on in the world, and I think it all over in my own way', it aims to show how a working musician mulls over and draws energy from the events of everyday life.We follow this internationally renowned pianist as she prepares for concerts and performs, both as a soloist and as part of a chamber ensemble; we experience the highs and lows of practising and the challenges of live performance, we see her planning masterclasses and interacting with both musicians and audiences. She casts her mind back to her childhood - practicing before school on cold Edinburgh mornings, playing 'Danny Boy' for a relative - and reflects on paintings, dance, books, sport and gardening.'A delight and a revelation...She writes with Schubertian intimacy, modesty and grace,' said the Independent of her first book, Beyond the Notes. Here Susan Tomes strives to unlock the secrets of great music and to understand its place in the wider world.SUSAN TOMES has won a number of awards for her recordings of chamber music. For fifteen years she was the pianist of Domus, and for another fifteen she has been the pianist of the Florestan Trio, one of the world's leading piano trios. She is the author of Beyond the Notes and A Musician's Alphabet. She writes occasionally for the Guardian and on a blog on her own website, www.susantomes.com.
Keywords: 21st Century (2001-2100); Pianist; Diary; Scotland